2019
DOI: 10.1093/geroni/igz038.1739
|View full text |Cite
|
Sign up to set email alerts
|

Mild Behavioral Impairment as a Predictor of Cognitive Functioning in Older Adults

Abstract: Background: Mild behavioral impairment (MBI) is considered to be a late life transitional state between normal aging and dementia that describes individuals who have persistent behavioral changes and/or psychiatric symptoms. Individuals with MBI are found to be at greater risk of dementia compared to those without these symptoms. Identifying how MBI might relate to different domains of cognition is of key importance, as it could be an early indicator of a future dementia diagnoses. Method: Secondary data analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 0 publications
1
5
0
Order By: Relevance
“…Longitudinal cohorts have demonstrated that an acceleration of decline in memory performance occurs 3-4 years before a diagnosis of MCI and 7 years before a diagnosis of AD, while for executive function an accelerated decline occurs 2-3 years before AD diagnosis 42,43 . The finding of small but significant associations between MBI and poorer memory and executive function performance is consistent with the evolving description of the cognitive profile of MBI [44][45][46] .…”
Section: Discussionsupporting
confidence: 86%
“…Longitudinal cohorts have demonstrated that an acceleration of decline in memory performance occurs 3-4 years before a diagnosis of MCI and 7 years before a diagnosis of AD, while for executive function an accelerated decline occurs 2-3 years before AD diagnosis 42,43 . The finding of small but significant associations between MBI and poorer memory and executive function performance is consistent with the evolving description of the cognitive profile of MBI [44][45][46] .…”
Section: Discussionsupporting
confidence: 86%
“… 22–32 Among these studies were seven that reported the prevalence of MBI among MCI patients, 22, 24–26, 28–30 five that reported the MBI prevalence among CN subjects, 26–28, 31, 32 and five that reported MBI prevalence among SCI or CN‐AR patients 22, 23, 25, 26, 32 . Two studies were performed in Japan, 25, 29 three studies in the USA, 28, 30, 32 two in Spain, 23, 24 two in Canada, 22, 31 and one each in Australia and the UK 26, 27 . More than half of the studies (6/11) were regarded as low quality mainly because of the lack of longitudinal follow‐up of subjects (Table 2).…”
Section: Resultsmentioning
confidence: 99%
“…With regard to the defining criteria for MBI, six studies used the Neuropsychiatric Inventory Questionnaire, three studies used the ISTAART criteria, and two studies used MBI‐C (Table 1). Thirteen studies were included in the systematic review to examine the effect of MBI in predicting cognitive deterioration, correlations to underling pathology or biomarkers, and genetic risks 20, 22–33 . No previous systematic review or meta‐analysis was identified.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations